Influence of lab lab (lablab purpureus) and dry bean (phaseolus vulgaris) intercrops with maize (zea mays l.) on maize grain yield and soil fertility status - Makgoga, Mahubane William (My University, 2013)
Maize (Zea mays L.) is the third most important cereal crop after wheat and rice in the world. Maize/legume intercropping system has become one of the solutions for food security among small scale maize producers due to unaffordability of chemical nitrogenous fertilizers and limited access to arable land. A study was conducted to determine the effect of maize/dry bean and maize/lablab intercropping on maize grain yield and soil fertility status. A field experiment was conducted during 2010/2011 and 2011/2012 growing seasons at the University of Limpopo experimental farm. Treatments included sole maize (ZM 521, an improved open pollinated variety, ex- CIMMYT), sole lablab (Rongai, indeterminate cultivar), sole dry bean (DBS 360, indeterminate Type II cultivar), maize/dry bean and maize/lablab intercrops arranged in randomized complete block design with five replications. Phosphorus (P) was applied on sole and intercropped maize at the rate of 30 kg P/ha in the form of superphosphate (10.5%P) at planting and 40 kg N/ha of nitrogen (N) was applied in the form of Limestone Ammonium Nitrate (LAN) (28%N) on both sole and intercropped maize four weeks after plant emergence. For maize and dry bean, grain yield, yield components and biomass were determined. Only biomass yield was measured for lablab. Soil samples were collected for soil analysis at the beginning and the end of the experiment The results showed that maize/lablab intercropping yielded significantly (P<0.05) lowered maize grain (1259.3 kg/ha) than sole maize and maize/dry bean intercropping which yielded maize grain of 2093.7 kg/ha and 2156.3 kg/ha, respectively. Sole dry bean yielded significantly (P <0.05) higher dry bean grain (1778.5 kg/ha) than intercropped dry bean (691.8 kg/ha). Rongai was only flowering by the time maize and dry bean matured hence only maize yield is reported for the Maize/lablab intercrop. Maize/dry bean intercropping was advantageous to sole cropping with a Land Equivalent Ratio (LER) of 1.42. The partial Land Equivalent Ratio (PLER) for maize in maize/lablab intercropping was 0.60. Dry bean was outcompeted by maize as calculated aggressivity value was positive at +0.64.The highest monetary value was achieved in sole dry bean and the lowest monetary value was found in intercrop dry bean. Soil TN, P, K, Ca, Mg and Na were reduced by both sole cropping and intercropping systems. Intercropping with lablab is likely to significantly lower maize yield under dryland conditions. Key words: dry bean, grain yield, Intercropping, lablab, maize, smallholder, soil fertility.
Thesis (MSc. Agriculture (Agronomy)) -- University of Limpopo, 2013
Keywords: Maize; Intercropping; Grain yield; Soil fertility; Corn -- Planting; Legumes; Intercropping; Dried beans